The Role of 4IR-5IR Leadership-Management in the Adoption of Formal Methods - John Andrew van der Poll (Systems, 2024)
Formal methods (FMs) have been cited as a viable methodology for developing high-quality software. However, the steep learning curve in efficiently using the underlying discrete mathematics and logic has hindered FMs’ adoption, leading to a decline in their initial interest in the 1980s. Traditionally, technical approaches have been pursued to address the FMs challenge. Having taken cognisance of a similar pre-4IR decline in AI, the researcher views FMs as technology and considers solutions at intersections of 4IR-5IR technology adoption, leveraged by the support of governors, termed leadership-management in this work. Following a qualitative research choice, scholarly literature is reviewed, and sets of qualitative propositions are defined to develop a conceptual framework for a 4IR-5IR leadership-management adoption of FMs. Aspects that emerged and are incorporated into the framework are cross-functional and executive levels of leadership, transformative, adaptive, and servant leadership styles, using FM tools that embed a high level of user experience, and 4IR technologies, augmented with 5IR human aspects. The framework is hoped to motivate a company’s leadership to contribute to technology and technical ICT-based decision-making increasingly. Future work in this area would involve securing input from practitioners and exercising the framework in an industrial setting.